MODERATE TEACHER PASCA PANDEMIC COVID-19 AT MADRASAH - Pelu, Hanafi (Uniqbu Journal of Social Sciences, 2022)
This study aims to explain the Moderate Teachers pasca Pandemic Covid-19 at Madrasah. The method in this paper is, ethnography to explain the language, culture, customs, and habits. The result of this research is; Moderate teachers always consider modification and formulating learning indicators and objectives in the moderation itself in pandemic Covid-19. Moderate teachers in formulating learning indicators and objectives, always fair, do not take sides with one or a group of students, are adjusted to conditions that are suitable for students and the school environment and facilities, are not excessive, and stay away from goals that can lead to violence